A simple method for assessment of atmospheric turbidity - MAJUMDAR, NC; WALMIK , NC; AGARWAL, BK (MAUSAM, 1985)
Based on the concept underlying Linke’s (1942) turbidity factor, T, a rational turbidity factor, Tr. was defined by Majumdar et.at. (1978), in which "Virtual variation with air mass" was minimised. Since both these factors include the effect of variable water vapour in the atmosphere, the same has been eliminated with the help of Schott red filter, RG-2. A new index of turbidity, T, has now been defined on the basis of two measurements of direct solar intensity with and without filter.